Multisystem frailty phenotypes and associated factors among older adults in Türkiye: A nationally representative study - Salim Yılmaz; Yusuf Çelik; Elif Cansu Kara (PLoS ONE, 2026)
Multisystem frailty, characterised by concurrent decline across motor, sensory, cognitive, and functional domains, remains a relatively understudied phenotype within ageing research. Evidence on its population-level distribution and associated factors, particularly in middle-income countries, is scarce. This study aimed to identify distinct multisystem frailty profiles among adults aged 50 years and older in Türkiye using nationally representative data. We analysed data from 26,905 adults aged 50 years and older drawn from the 2023 Turkish Statistical Institute Elderly Statistics Survey. Latent profile analysis was employed using eight indicators capturing motor, sensory, cognitive, and functional domains. Survey-weighted multinomial logistic regression models were used to examine sociodemographic and health-related factors associated with frailty profile membership. Three multisystem frailty profiles were identified: robust (weighted prevalence 51.4%), intermediate frailty (33.7%), and severe multisystem frailty (14.8%). Severe frailty was substantially more common among women than men (20.0% vs 9.1%) and among adults aged 65 years and older compared with those aged 50–64 years (24.7% vs 8.9%). Health- and lifestyle-related factors accounted for the largest share of explained variance in profile membership (51.9%). Poor or very poor self-rated health exhibited exceptionally strong associations with severe frailty (odds ratio range 47.89–95.78), with corresponding E-values exceeding 90. Multisystem frailty affects nearly half of adults aged 50 years and older in Türkiye and displays pronounced inequalities by age, sex, and perceived health status. These findings underscore the importance of multidomain assessment approaches and highlight potentially modifiable social and health-related factors associated with frailty vulnerability in ageing populations.